Pengaruh Kombinasi Dosis Pupuk Vermikompos dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Kubis Bunga (Brassica oleracea var. botrytis L) - Wagiono; Amalia Dwi Putri; Vera Oktavia Subardja; Lukman Hakim (Faculty of Agriculture University of Singaperbangsa Karawang, 2021)
This research was conducted at the Balai Pengkajian Teknologi Pertanian (BPTP), South Jakarta. Potential yield of flower cabbage (Brassica oleracea var. Botrytis L.) in Indonesia has decreased, this can be achieved by using a combination of inorganic fertilizers and organic fertilizers to increase the growth and yield of flower cabbage as well as maintain soil health. The purpose of this study was to determine the effect of a combination of vermicompost and NPK fertilizers on the growth and yield of flower cabbage. This study used a single factor randomized block design (RBD) with 12 treatments of combination doses of vermicompost and NPK fertilizers, repeated 3 times. The treatments consisted of a combination of vermicompost fertilizer (160 g, 320 g, 480 g and 640 g) combined with NPK fertilizer (12.8 g, 10.2 g and 7.7 g). The results were analyzed using the F test at the 5% level to determine the best treatment, followed by the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the application of vermicompost fertilizer combined with NPK increased plant height, leaf number, and pH, head weight, crop diameter and stover weight. Treatment J with a combination of vermicompost dosage of 640 g and NPK fertilizer 12.8 g obtained the highest yield on the parameters of plant height, number of leaves, weight of head, diameter of crop and weight of cabbage flower stalk. The results achieved from this study were the dosage treatment of vermicompost and NPK fertilizers had a significant effect on the growth and yield of flower cabbage. Keywords: Vermicompost, NPK, Flower Cabbage